Influence of halal logo on muslim consumer decision making / Henie Nabila A.Rahim - A.Rahim, Henie Nabila (2013)
The purpose of this study is to identify the influence of halal logo on Muslim consumers' decision making and to determine the importance of halal logo for Muslim consumers' decision making. While the scope of this is bounded and delimited by a number of predetermined limits in which it only focus on a fraction of employees in Plant Operation Division of Petronas Gas Berhad, Kerteh, Terengganu which are the employees in Maintenance Services Department. Besides that, this study is also focused on the Muslim workers in this department only. This study is restricted to focus only on one factor which is halal logo. The method for this study is a structured questionnaire used to elicit responses from consumers using a stratified random sampling technique. A total of 30 responses were received. The findings indicated that the p > 0.05. Therefore, the hypothesis is rejected and it can be concluded that there is no significant correlation between halal logo and Muslim consumers' decision making. It is recommended to conduct future study to escalate the sample size and population by wider the area of the survey and may include a few more factors. JAKIM and media involvement also is recommended to monitor and promote halal logo.